2011
DOI: 10.1002/cmdc.201100069
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Competitive Apelin Receptor (APJ) Antagonist

Abstract: The apelin receptor (APJ) is a class A G-protein-coupled receptor (GPCR) and is a putative target for the treatment of cardiovascular and metabolic diseases. Apelin-13 (NH₂-QRPRLSHKGPMPF-COOH) is a vasoactive peptide and one of the most potent endogenous inotropic agents identified to date. We report the design and discovery of a novel APJ antagonist. By using a bivalent ligand approach, we have designed compounds with two 'affinity' motifs and a short series of linker groups with different conformational and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 50 publications
0
61
0
1
Order By: Relevance
“…The inhibitory effect of apelin on platelet aggregation involves the APJ receptor Using 2 APJ antagonists, apelin-F13A (F13A) 23 and MM54, 24 we found that F13A or MM54 alone did not significantly modify platelet aggregation. In contrast, inhibition of platelet aggregation by apelin-13 was completely prevented by F13A and partially prevented by MM54 ( Figure 1F).…”
Section: Resultsmentioning
confidence: 89%
“…The inhibitory effect of apelin on platelet aggregation involves the APJ receptor Using 2 APJ antagonists, apelin-F13A (F13A) 23 and MM54, 24 we found that F13A or MM54 alone did not significantly modify platelet aggregation. In contrast, inhibition of platelet aggregation by apelin-13 was completely prevented by F13A and partially prevented by MM54 ( Figure 1F).…”
Section: Resultsmentioning
confidence: 89%
“…In a study carried out to understand the molecular features of apelin required for a signalling response from APJ, three cyclic analogues of apelin-12 (C1, C3 and C4) have proved to be novel APJ agonists, but are less potent than (Pyr 1 )apelin-13 in the inhibition of cAMP accumulation and in the phosphorylation of protein kinase B (Akt) and ERK1/2 (Hamada et al 2008), while the use of a bivalent ligand approach incorporating a b-turn within the RPRL region of apelin, which is critical in APJ ligand recognition, has resulted in the identification of a competitive antagonist at APJ (Macaluso et al 2011).…”
Section: Cyclic and Other Apelin Analoguesmentioning
confidence: 99%
“…Compellingly, the conserved structural features of the apelin isoforms have been directly employed in design of peptide-based AR antagonists (Macaluso and Glen 2010;Macaluso et al 2011), and agonists (Murza et al 2012). Despite the clear importance of the apelin C-terminal dodecapeptide region, the presence of multiple apelin isoforms in the body suggests an evolutionary purpose.…”
Section: Apelin-induced Signallingmentioning
confidence: 99%